Dzieciństwo jako miejsce traumatyczne w wybranych utworach Ludwika Tiecka i E.T.A. Hoffmanna - Dylewska, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article attempts to depict the phenomenon of childhood as a "traumatic place" on the basis of the idea of a multi-layered concept of childhood created in (German) Romanticism. The following four short stories: "The Fair-Haired Eckbert" and "The Seven Wives of Bluebeard" by Ludwig Tieckand "The Strange Child" and "The Sandman" by E.T.A. Hoffmann were subjected to a detailed analysis.
Keywords: trauma; zespół stresu pourazowego (PTSD); romantyzm; dzieciństwo; post-traumatic stress disorder (PTSD); romanticism; childhood